Factors that contribute to HIV-related stigma and discrimination within the Christian faith community : a survey of the Christ Embassy Church in Windhoek - Senzanje, Nomusa (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.